Personality aspect of professional activities of a higher school teacher - Kozlovskyi, Yurii; Kravets, Svitlana (Lviv Politechnic Publishing House, 2017)
The article clarifies the fact that the issue of studying the personality development of higher school teachers in the context of their professional activity is relevant. Readiness for professional activity is considered as a system characterized by appropriate coefficients, the complex consideration of which allows obtaining reliable information about the real level of teachers’ professional work. It is expedient to present the features of the professional teaching staff of higher educational institutions in three categories: a practising teacher, a teacher-researcher and a scientist in the field of specialization of an educational institution. The higher school teachers’ scientific and pedagogical activities in the context of modern morality are an important component of their professional competence, substantially affecting the results of their teaching and research activities. It is considered as the realization of the idea of humanization of science and education.
Keywords: higher school; teacher; professional activity; personality aspect; personality; readiness for professional activity; teacher-practitioner; teacher-researcher; scientist in the field; scientific and pedagogical activity